Erratum: MARTIN, JON, SUBLETTE, JAMES E. & CALDWELL, BROUGHTON A. (2010) Description of Chironomus quinnitukut, n. sp., closely related to the C. decorus group in North America, with characterization of an additional larval form from halobiontic habitats. Zootaxa, 2716, 29–41. - Martin, James E. Jon Sublette; Caldwell, Broughton A. (Zootaxa, 2011)
(Erratum)